Hemodynamic Functions of Fenestrated Stent Graft under Resting, Hypertension, and Exercise Conditions - Kandail, Harkamaljot Singh; Hamady, Mohamad; Xu, Xiao Yun (Frontiers in Surgery, 2016)
The aim of this study was to assess the haemodynamic performance of a patient-specific Fenestrated Stent-Graft (FSG) under different physiological conditions, including normal resting, hypertension, and hypertension with moderate lower limb exercise. A patient-specific FSG model was constructed from computed tomography images and was discretised into a fine unstructured mesh comprising of tetrahedral and prism elements. Blood flow was simulated using Navier-Stokes equations and physiologically realistic boundary conditions were utilised to yield clinically relevant results. For a given cycle-averaged inflow of 2.08 L/min at normal resting and hypertension conditions, approximately 25% of flow was channelled into each renal artery. When hypertension was combined with exercise, the cycle-averaged inflow increased to 6.39 L/min but only 6.29% of this was channelled into each renal artery which led to a 438.46% increase in the iliac flow. For all the simulated scenarios and throughout the cardiac cycle, the instantaneous flow streamlines in the FSG were well organised without any notable flow recirculation. This well organised flow led to low values of Endothelial Cell Activation Potential (ECAP), which is a haemodynamic metric used to identify regions at risk of thrombosis. The displacement forces acting on the FSG varied with the physiological conditions and the cycle-averaged displacement force at normal rest, hypertension, and hypertension with exercise was 6.46 N, 8.77 N and 8.99 N, respectively. The numerical results from this study suggest that the analysed FSG can maintain sufficient blood perfusion to the end organs at all the simulated conditions. Even though the FSG was found to have a low risk of thrombosis at rest and hypertension, this risk can be reduced even further with moderate lower limb exercise.